REPRESENTASI BUDAYA WOLIO DALAM NOVEL PEREMPUAN WOLIO KARYA KRISNI DINAMITA - Mustika Mustika; Wa Ode Halfian (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
Krisni Dinamita presents information about Wolio’s culture in her novel entitle Wolio’s Women. However, not all readers of the novel understand about Wolio’s culture, so that the researcher intends to examine how Wolio’s culture represents in the novel. This research analyzes sign of Wolio’s culture in the novel using Charles Sanders Pierce Semiotics which divides sign according to the relation of sign with its references to: icons, indexes, and symbols. The aim of this research is to describe and explain the representation of Wolio’s culture in the novel. The results of this research show that there are eight icons of Wolio’s culture in the novel, namely: the Buton Palace, pekande-kandea, kabanti, kadandio, mia patamia, “yinda-yindamo arataa somanamo karo, yinda-yindamo karo somanamo lipu, yinda-yindamo lipu somanamo sara, yinda-yindamo sara somanamo agama”, bisa, lebe, and “kapakawana pitumalona, kapakawana patapuluna, kapakawana saatuna”. However, there are four indexes of Wolio’s culture, namely: pesoloi, lawati, malona kompa, and oputalinga rusa. Likewise, there are five symbols of Wolio’s culture found in the novel: kawi pobaisa, kaomu, walaka, papara, and haroa.